Orwell’s Animal Farm: Ideological State Apparatuses and the Crisis of the Modern State - Al-Aghberi, Munir Ahmed (Journal of English Language and Literature (ISSN: 2368-2132), 2018)
The present paper explores the crisis of the modern democratic state based on Althusser’s concept of the Ideological State Apparatuses and Chomsky’s investigation into the suspicious role of the media. Orwell’s novel Animal Farm was examined by way of casting the light on the junctures of intersection between history and culture. Re-reading the novel through the perspective of Althusser’s ISA and Chomsky’s experienced lens help understand the way of the modern world where the various media means drive the masses into the end determined by the ruling business groups.